Sonhos e a vida na rua: fronteiras do corpo e alma - Cruz, Luciana Carvalho de Brito (2019)
This research is based on dreams and onirics images that where collected in the dialogue with womens who live in the streets of São Paulo. A subjective testimonial mixed with realities that are shared in the city. In this rapprochement between city and soul, the discussion points to conflicts, exchanges, creation and the imagination of different persons in their singularity. The goal is to open the politic and social debate from the view of the subjectivity in the way to break the natural conception of the life in the streets in the normativity way of thinking it, to the concret to the symbolic. This dialogue is also a intent to consider the way that public policy and the selfcare about people in this situation are thouth, and to create a new way of discussion and new strategies of caring for people who lives in the streets and share the space whit us